Hyperpyrexia During Anaesthesia. Issue 5618 (7th September 1968) - Harrison, G. G.; Biebuyck, J. F.; Terblanche, J.; Dent, D. M.; Hickman, R.; Saunders, S. J.
Abstract : Work in pigs has shown that malignant hyperpyrexia during anaesthesia may occur without suxamethonium having been given. A virtually constant feature in reported cases and in our own observations is that all subjects developing hyperpyrexia had received nitrous oxide and halothane.